Resisting Lazy Political Analysis: Crafting a Feminist Curiosity to Make Sense of International Politics - Cynthia Enloe (Alternatif Politika)
It is so easy, so enticing, I now realize, to skip gender questions. Just talk about any state’s military without wondering about marriage - or rape or homophobia. Just track recruitment into insurgent armed militias without investigating contested masculinities. Demonstrate your analytical sophistication by referring to multiple actors: “state elites,” “the media,” “factory workers,” “bankers,” “youth,” “refugees,” “party strategists,” “NATO officials,” “religious clerics,” “contractors,” “peace activists, “arms manufacturers,” “judges,” and “voters.”